Inovasi Produk Ramah Lingkungan: Pembuatan Lilin Dari Daun Mangrove Avicennia Marina Untuk Pemberdayaan Masyarakat Pesisir - Azalia Fajri Yasin; Nurbia; Irnawati; Riskawati; Nur Abu; Umar Rusli Marasabessy; Azwar Rahmatullah; Mierta Dwangga; Mardiah Gani; Putri Mambraku (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service iitiative aims to develop an eco-friedly product utilizing local natural resources, specifically Avicenna marina mangrove leaves as raw material for candle production. The innovattion is driven by the ecological and economic potential of mangrove plants, which have not yet been optimally utilized, alongside the need for alternative income sources for coastal communities. The implementation method includes literature review, processing mangrove leaves through boiling and mixing with basic candle materials, production training for coastal residents and mentoring of small-scale environmentally based enterprises.The results of the activity indicate that the candles produced have stable flame performance, a natural aroma and aesthetically appealing qualities suitable for commercial sale. This program serves as an inital step in developing a creative economy model based on mangrove ecosystes, which can be replicated in other coastal regions. Through a collaborative and sustainable approach, this initiative demonstrates that environmental conservation and social empowerment can go hand in hand.